Chaperone-Mediated Autophagy in the Light of Evolution: Insight from Fish. (21st May 2020) - Lescat, Laury; Véron, Vincent; Mourot, Brigitte; Péron, Sandrine; Chenais, Nathalie; Dias, Karine; Riera-Heredia, Natàlia; Beaumatin, Florian; Pinel, Karine; Priault, Muriel; Panserat, Stéphane; Salin, Bénédicte; et al.
Abstract: Chaperone-mediated autophagy (CMA) is a major pathway of lysosomal proteolysis recognized as a key player of the control of numerous cellular functions, and whose defects have been associated with several human pathologies. To date, this cellular function is presumed to be restricted to mammals and birds, due to the absence of an identifiable lysosome-associated membrane protein 2A (LAMP2A), a limiting and essential protein for CMA, in nontetrapod species. However, the recent identification of expressed sequences displaying high homology with mammalian LAMP2A in several fish species challenges that view and suggests that CMA likely appeared earlier during evolution than initially thought. In the present study, we provide a comprehensive picture of the evolutionary history of the LAMP2 gene in vertebrates and demonstrate that LAMP2 indeed appeared at the root of the vertebrate lineage. Using a fibroblast cell line from medaka fish ( Oryzias latipes ), we further show that the splice variant lamp2a controls, upon long-term starvation, the lysosomal accumulation of a fluorescent reporter commonly used to track CMA in mammalian cells. Finally, to address the physiological role of Lamp2a in fish, we generated knockout medaka for that specific splice variant, and found that these deficient fish exhibit severe alterations in carbohydrate and fat metabolisms, in consistency with existing data in mice deficient for CMA in liver. Altogether, our data provide the first evidence for a CMA-like pathway in fish and bring new perspectives on the use of complementary genetic models, such as zebrafish or medaka, for studying CMA in an evolutionary perspective.